Strategi Dakwah berbasis Kesetaraan Gender Bu Nur Rofiah melalui Akun Media Sosial @ngaji_kgi - Febrianto, Mohamad; Romadhoni, Berlianti Kaarunia; Saputro, Dimas Setyawan (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2025)
This study analyzes Bu Nur Rofiah's digital da'wah strategy in promoting gender equality through social media on the Instagram account Ngaji Keadilan Gender Islam (@ngaji_kgi). The phenomenon of limited participation of women in da'wah on digital platforms creates a representation gap in religious discourse, especially regarding gender equality issues that are often overlooked in mainstream conventional da'wah. Nur Rofiah, as a female activist and intellectual, utilizes social media as an alternative space to build narratives of gender equality based on progressive interpretations of Islamic teachings. Using a qualitative-descriptive approach, this study explores how Nur Rofiah transforms traditional religious discourse into inclusive and gender-responsive da'wah messages through various digital platforms. The findings show that Bu Nur Rofiah's digital da'wah not only functions as an alternative narrative to patriarchal interpretations but also as a space for the intellectual empowerment of Muslim women. Her dialogical and argumentative communication strategies facilitate the formation of an epistemic community that supports the gender equality agenda within the framework of Islamic values. This research contributes to understanding the role of social media in democratizing religious discourse and empowering women's voices in digital public spaces.